77.8k views
0 votes
Write the result of (4+9i)(7-4i) in a+bi form​

User Jinelle
by
4.6k points

2 Answers

6 votes

ANSWER


(4 + 9i)(7 - 4i) = 64 + 47i

EXPLANATION

The given complex number expression is:


(4 + 9i)(7 - 4i)

We expand using the distributive property to get;


(4 + 9i)(7 - 4i) = 4(7 - 4i) + 9i(7 - 4i)


(4 + 9i)(7 - 4i) = 28- 16i + 63i - 36 {i}^(2)

Recall that,


{i}^(2) = - 1

Our expression now simplifies to:


(4 + 9i)(7 - 4i) = 28 + 47i + 36


(4 + 9i)(7 - 4i) = 64 + 47i

User Romasz
by
4.6k points
3 votes

Answer:
64+47i

Explanation:

Given the Complex numbers multiplication:


(4+9i)(7-4i)

You need to follow these steps:

1. Apply Distributive property:


(4+9i)(7-4i)=(4)(7)+(4)(-4i)+(9i)(7)+(9i)(-4i)=28-16i+63i-36i^2

2. You need to remember that:


i=√(-1)\\\\i^2=-1

Then, you need to substitute
i^2=-1:


28-16i+63i-36(-1)=28-16i+63i+36

3. Finally, add the like terms:


64+47i

User Tim Hong
by
5.7k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.